2021
DOI: 10.4103/ijmr.ijmr_2020_18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between increased serum & synovial fluid decorin levels & knee osteoarthritis

Abstract: Background & objectives: Decorin is a proteoglycan that plays a role in the binding of collagen and has an important role in the pathogenesis of osteoarthritis (OA). This study was aimed to determine serum and synovial fluid decorin levels in patients with knee OA and to investigate whether these levels were associated with OA and the Western Ontario and McMaster Universities Osteoarthritis (WOMAC) score. Methods: In this prospective study 88 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…In the present study, as regard to age, we found no statistically significant differences between the patient group, with a mean of 52.54±9.11, compared with the control group, with a mean of 49.22±8.89, with P value >0.05. This is consistent with Ozlar [18] , who revealed no significant differences in their study between patients regarding age with a mean age of 63.04±5.68 and controls with a mean age of 59.94±6.50.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, as regard to age, we found no statistically significant differences between the patient group, with a mean of 52.54±9.11, compared with the control group, with a mean of 49.22±8.89, with P value >0.05. This is consistent with Ozlar [18] , who revealed no significant differences in their study between patients regarding age with a mean age of 63.04±5.68 and controls with a mean age of 59.94±6.50.…”
Section: Discussionsupporting
confidence: 91%
“…A positive correlation between serum decorin levels and WOMAC was also discovered in this study, with p-value <0.05. This is in agreement with Ozlar [18] who studied 44 knee OA patients and investigated levels of serum decorin and their relationship with clinical indices. He found significantly elevated serum decorin levels in knee OA patients relative to the control group and a positive association between levels of serum decorin and WOMAC score.…”
Section: Discussionsupporting
confidence: 90%
“…The release of soluble forms of biglycan or decorin from the ECM of cartilage into the synovial fluid following tissue injury may act as an internal danger signal [ 64 ]. Soluble biglycan and decorin in synovial fluid and serum can be detected using ELISA [ 63 , 64 , 78 , 79 ]. Barreto et al [ 63 ] observed high levels of biglycan in advanced OA, concluding that soluble biglycan can serve as a mediator of OA cartilage as well as a potential biomarker.…”
Section: Role Of Proteoglycans In Chondral Injuriesmentioning
confidence: 99%
“…The role of decorin in osteoarthritis is complex. It was reported that serum decorin levels were elevated in OA and could be a risk factor for OA [ 99 ]. However, studies in mouse models showed different results.…”
Section: Decorin In Autoimmune and Inflammatory Diseasesmentioning
confidence: 99%